Thrips ornamental plants in Ukraine - Баранова, С. С. (Problems of Environmental Biotechnology, 2015)
Considerably damage to the thrips different plants necessitates the search for new methods of protecting plants from pests and mechanical action on thei. ability to transfer viral pathogens. And without fully studying the species composition of plant thrips is not possible to minimize their negative impact. The main three types of thrips most damaging ornamental plants, is western flower thrips , thrips palmi and echinothrips.